Synthesis and characterization of transition metal complexes with aspirin thiourea ligands - Enis Nadia, Md. Yusof. (Universiti Malaysia Sarawak (UNIMAS), 2011)
The focus of this research is to react aspirin thiourea ligands with 3d transition metal (II) ion. There are two types of ligands that have been synthesized which are chloroaspirin with amine and chloroaspirin with amino acids. The ligands have been obtained by the condensation reaction between amine group and amino group. Then, transition metal complexes were synthesized by the direct reaction of 3d transition metal salts with aspirin thiourea ligands. Pure compounds of ligands and their metal complexes were characterized with FTIR, UVVisible, 1H NMR and 13C spectroscopy, and molar conductivity. All FTIR spectra of the ligands and transition metal complexes shows v(N-H), v(C=O) (carbonyl), v(C=O) (carboxylic), v(C=S), and v(C-N) absorption bands. The important 1H NMR chemical shift that were observed are δ(N1-H), δ(N2-H), δ(Ar-H), and δ(OH) chemical shift. Aspirin thiourea complexes were screened for their antibacterial activity using E. coli. 120 ppm is minimum inhibition concentration (MIC) values of the compounds 12 toward the bacteria were determined.